Analisis Fraud Triangle Dalam Mendeteksi Kecurangan Laporan Keuangan Pada Perusahaan BUMN Non Keuangan Di Indonesia - Akbar, Muhammad Vacrizal Mirazi; Utary, Dr. Hj. Anis Rachma; ginting, Yoremia Lestari Br. (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Abstract : M. Vacrizal Mirazi Akbar. Fraud Triangle Analysis in Detecting Financial Reports Fraud in Non-Financial BUMN Companies In Indonesia. This study was conducted under the guidance of Hj. Anis Rachma Utary and Yoremia Lestari br. Ginting.The financial reports have become an important instrument in the operation of a company. The financial condition of the company can be reflected in the company's financial reports. However, there are many loopholes in the financial reports that give certain people the possibility to commit fraud on the financial reportsThis study aims to obtain empirical evidence on the effectiveness of fraud triangle in detecting fraudulent financial reports. The variables of fraud triangle are financial stability which proxied by ACHANGE, external pressure which proxied by LEVERAGE, financial targets proxied with ROA, nature of industry proxied by RECEIVABLE, monitoring proxied by the ratio of independent audit committee and rationalization proxied by AUDCHANGE. Detection of fraudulent financial reports in this study used the Beneish M-Score analysis.The sample selection procedure was using purposive sampling in the population of non-financial BUMN companies in Indonesia, and then researcher obtained 24 samples of the company for 3 years of eligible observations. The hypothesis tests were using logistic regression analysis, with SPSS application version 23. This study used 2013-2015 panel data.The results of this study indicate that financial stability, nature of industry, and rationalization has significant effects on fraudulent financial reports. On the other hand, external pressure, financial target, and monitoring have no significant effect on fraudulent financial reports.Keywords : Fraud Triangle, Beneish M-Score, Financial Stability, External Pressure, Financial Target, Nature of Industry, Monitoring, Rationalization.Abstrak M. Vacrizal Mirazi Akbar. Analisis Fraud Triangle Dalam Mendeteksi Kecurangan Laporan Keuangan Pada Perusahaan BUMN Non Keuangan Di Indonesia. Penelitian ini dilaksanakan dibawah bimbingan Hj. Anis Rachma Utary dan Yoremia Lestari br. GintingLaporan keuangan menjadi suatu instrumen penting dalam operasional suatu perusahaan. Kondisi perusahaan secara financial dapat tercermin dalam laporan keuangan perusahaan. Namun, terdapat banyak celah dalam laporan keuangan yang dapat menjadi ruang bagi manajemen dan oknum tertentu untuk melakukan kecurangan (Fraud) pada laporan keuangan.Penelitian ini bertujuan untuk memperoleh bukti empiris mengenai efektivitas dari fraud triangle dalam mendeteksi kecurangan laporan keuangan. Variabel-variabel dari fraud triangle adalah financial stability yang diproksikan dengan ACHANGE, external pressure yang diproksikan dengan LEVERAGE,  financial target yang diproksikan dengan ROA, nature of industry yang diproksikan dengan RECEIVABLE, monitoring yang diproksikan dengan rasio komite audit independen dan rationalization yang diproksikan dengan AUDCHANGE. Pendeteksian kecurangan laporan keuangan dalam penelitian ini menggunakan analisis Beneish M-Score.Prosedur penyeleksian sampel menggunakan purposive sampling pada populasi perusahaan BUMN non keuangan di Indonesia, dan selanjutnya diperoleh 24 sampel perusahaan selama 3 tahun pengamatan yang memenuhi persyaratan. Pengujian hipotesis menggunakan analisis regresi logistik, dengan aplikasi SPSS versi 23. Penelitian ini menggunakan data panel tahun 2013-2015.  Hasil penelitian ini menunjukkan bahwa financial stability, nature of industry, dan rationalization berpengaruh signifikan terhadap kecurangan laporan keuangan. Sementara itu, external pressure, financial target, dan monitoring tidak berpengaruh signifikan terhadap kecurangan laporan keuangan.Kata Kunci: Fraud Triangle, Beneish M-Score, Financial Stability, External Pressure, Financial Target, Nature of Industry, Monitoring, Rationalization